Intensive Care Management of a Patient With Pickwickian Syndrome, Obesity, and Congestive Heart Failure - Mada Oktav Cakradwipa; Bowo Adiyanto; Erlangga Prasamya (JAI (Jurnal Anestesiologi Indonesia), 2026)
Background: Pickwickian Syndrome is a condition of alveolar hypoventilation characterized by hypercapnia due to decreased ventilatory drive and capacity caused by obesity. The prevalence of this syndrome aligns with the increasing obesity rate in various countries, especially developed nations, and is associated with obstructive sleep apnea (OSA). Individuals with OSA have a 20–30% risk of developing Pickwickian Syndrome.Case: A 36-year-old male, weighing 160 kg and height 168 cm (body mass index (BMI): 56.69 kg/m²), presented with progressive dyspnea for one week. He had a history of hypertension and heart disease, managed with medication. On arrival at the emergency department (ED), he showed signs of hypoxemia with SpO₂ 80%, which improved to 97% after oxygen therapy with a non-rebreathable breathing mask at 10 L/min. Blood gas analysis revealed partially compensated respiratory acidosis. A Chest X-ray showed bilateral pulmonary edema and cardiomegaly. A diagnosis of Pickwickian Syndrome with congestive heart failure was established. The patient was managed in the intensive care unit (ICU) for 13 days with non-invasive ventilation (NIV) as ventilatory support.Discussion: This case illustrates the complex interplay among morbid obesity, hypoventilation, and cardiac dysfunction. Obesity leads to increased airway resistance and impaired thoracic compliance, resulting in reduced effective ventilation and CO₂ retention. When combined with congestive heart failure, pulmonary edema, and further hypoxemia may ensue. The successful outcome in this case underlines the importance of early diagnosis, targeted respiratory support, and effective fluid management.Conclusion: Intensive care of the patients with Pickwickian Syndrome and congestive heart failure requires a holistic multidisciplinary approach. Optimizing oxygenation, maintaining strict fluid balance, and administering appropriate pharmacologic therapy are crucial to preventing complications and improving prognosis.